AB0247 INSIGHTS INTO ADHERENCE AND PATIENT-INITIATED MONOTHERAPY FOR RHEUMATOID ARTHRITIS VIA A GLOBAL SURVEY OF PATIENTS, CAREGIVERS AND PHYSICIANS. (June 2019) - Galloway, James; Dikranian, Ara; Koehn, Cheryl L.; Gruben, David C.; Woolcott, John; Strengholt, Sander
Abstract : Background: Treatment satisfaction and adherence remain issues affecting outcomes for patients (pts) with rheumatoid arthritis (RA). A better understanding of the reasons for non-adherence, and differences between pt, caregiver and healthcare professional (HCP) views on adherence, may improve decision-making and outcomes. Objectives: To survey pts, caregivers and HCPs, in order to investigate pt behaviours and attitudes, and communications between pts, caregivers and HCPs regarding adherence to RA therapy. Methods: Surveys were conducted online by Harris Poll between Oct and Nov 2018, among pts/caregivers and HCPs from Australia, Brazil, Canada, Germany, Japan, Spain, Taiwan, UK and US. The pt survey included pts aged ≥18 years with a diagnosis of RA who had taken conventional synthetic disease-modifying antirheumatic drugs (csDMARDs) with biological (b)DMARDs in the past 3 years. The caregiver survey included adults aged ≥18 years who lived with/provided care to a spouse/family member with RA and were involved in ≥2 care activities for a pt with RA who had taken csDMARDs with bDMARDs in the past 3 years. The HCP survey included responses from licensed rheumatologists (orthopaedists in Japan) who saw ≥10 pts with moderate/severe RA per month, ≥10% of whom had been prescribed a bDMARD. A post-weight was applied to raw data to adjust for the relative adult population size of each country vs the total for all 9 countries surveyed. Results: In total, 900 pts, 714 caregivers and 840 HCPs responded to the surveys. Overall, 50% of both pts and caregivers reported that pts always took their current RA prescription medications exactly as directed. However, 67% of pts reported that they had not always adhered to dosing regimens (most common deviations: skipping doses [45%]; extending time between doses [44%]; taking other medications without HCP direction [38%]; taking less than the prescribed dose [34%]; dose splitting [31%]; and stopping medications altogether [28%]). Among HCP respondents, 98% reported asking pts about adherence to RA medication, even though 61% felt there was no way of knowing if pts were taking medications as prescribed and, overall, HCPs responded that 64% of pts did not always take RA medication as prescribed. While 87% of HCPs agreed that bDMARDs were most effective when taken in combination with csDMARDs and 92% reiterated this to pts, 62% were concerned that pts take bDMARDs without csDMARDs. Pts and caregivers reported that pts often stopped taking csDMARDs; however, HCPs underestimated the number of non-adherent pts (Figure A ). The most common reason given by pts and caregivers for non–adherence to RA medication was difficulty in remembering to take medication; however, concerns about feeling ill and potential side effects were also common (Figure B). Despite this, 47% of pts and 51% of caregivers responded that pts often don't share all side effects caused by their RA medication with HCPs, while 38% of HCPs believed that pts did not inform them of all side effects. Conclusion: This study from a large, multinational cohort of pts with RA, caregivers and HCPs describes medication adherence patterns. Pts on bDMARDs often did not take their background csDMARDs; however, the extent of pt non-adherence was underestimated by HCPs. These results highlight gaps in communication and understanding of non-adherence between pts, caregivers and HCPs. Acknowledgement: Study sponsored by Pfizer Inc. Medical writing support was provided by Anthony G McCluskey, PhD, of CMC Connect and funded by Pfizer Inc. Disclosure of Interests: James Galloway Consultant for: Pfizer Inc, Ara Dikranian Consultant for: AbbVie, Pfizer Inc, Speakers bureau: AbbVie, Pfizer Inc, Cheryl L Koehn Shareholder of: Arthritis Consumer Experts, Grant/research support from: Canadian Institutes of Health Research, Arthritis Research Canada, St. Paul's Hospital, Employee of: Arthritis Consumer Experts, David C Gruben Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, John Woolcott Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, Sander Strengholt Shareholder of: Pfizer Inc, Employee of: Pfizer Inc